2013
DOI: 10.1002/hup.2327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐dose mirtazapine on driving performance in healthy volunteers

Abstract: Mirtazapine 7.5 mg did not cause driving impairment compared with mirtazapine 15 mg, while both doses of mirtazapine produced subjective somnolence. The increase in mirtazapine had no detrimental effects on psychomotor performance. Initial low-dose mirtazapine may be safer for automobile driving than the normal starting dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Furthermore, our study also showed that a daily dosing regimen of MIR at 15 mg/kg or more decreased spontaneous locomotor activity within 10 minutes of administration, with a gradual decrease in sedative effects, 10,15 while balance and motor coordination were unaffected. Conversely, TRZ impaired motor activity, balance, and motor coordination quickly (within 5 minutes) and for up to 60 minutes.…”
Section: Experiments 2: Effect Of Chronic Mir Dosing On Sedationsupporting
confidence: 66%
See 2 more Smart Citations
“…Furthermore, our study also showed that a daily dosing regimen of MIR at 15 mg/kg or more decreased spontaneous locomotor activity within 10 minutes of administration, with a gradual decrease in sedative effects, 10,15 while balance and motor coordination were unaffected. Conversely, TRZ impaired motor activity, balance, and motor coordination quickly (within 5 minutes) and for up to 60 minutes.…”
Section: Experiments 2: Effect Of Chronic Mir Dosing On Sedationsupporting
confidence: 66%
“…10 Additionally, Poyurovsky et al 15 have reported that MIR given in doses of 15 mg/kg is well tolerated and causes only mild and transient sedation.…”
Section: Experiments 1: Effect Of Acute Mir Dosing On Sedationmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of impairment reached a clinically relevant level, as the observed SDLP increment relative to placebo was comparable to that seen with a BAC of 0.05%. Consistently, after mirtazapine 15 and 30 mg, driving impairment was also found in the driving simulator studies Iwamoto et al, 2013). After 1 or 2 weeks of daily treatment with mirtazapine, driving impairment was much less pronounced, and it differed between studies whether significant differences from placebo were found.…”
Section: Discussionsupporting
confidence: 51%
“…There are currently 36 types of confirmed DS . As each research group uses a DS for a specific purpose, there is no unified scenario (e.g., highway, urban roads).…”
Section: Resultsmentioning
confidence: 99%